Empirical analysis of occupational hierarchies - Ferrall, Christopher [Verfasser] (My University, 1997)
"Using data on U.S. engineers and the position of engineering jobs within firms, this paper estimates a model of hierarchies within firms. The model extends Rosen's (1982) model of recursive production to two skills and multiple hierarchy levels. The model generates an empirical model that is nested within a general Roy (1951) model of self-selection. Maximum likelihood estimates of the parameters of the production technology and the skill-experience profiles are estimated. The results suggest that approximately two- thirds of changes in employment shares across hierarchy levels across time are explained by demographic shifts in the stock of engineering skills. Most of the returns to experience and to assignment to higher hierarchy levels within firms are caused by skill accumulation and self-selection rather than technological differences across hierarchy levels." (author's abstract, IAB-Doku) ((en)) Unter Nutzung empirischer Daten entwickeln die Autoren ein Modell zu Selektionsprozessen und innerbetrieblichen Hierarchien bei Karriereverläufen von Ingenieuren. (IAB)
Keywords: G 2.3.1 Arbeitsteilung & -organisation; S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; G 1.2.2.1 Lohn- & Tarifsysteme; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; I 2.3.2 Nordamerika; Innerbetriebliche Hierarchie; Modell; Ingenieur; Lohnhöhe; Berufsproblem; Berufsverlauf; Beruflicher Aufstieg; Quantitative Angaben; USA